ЗАМОНАВИЙ ТИЛШУНОСЛИКДА “ТУРМУШ” КОНЦЕПТИ ҚЎЛЛАНИШИНИНГ СЕМАНТИК ХУСУСИЯТЛАРИ - Samatova Zulhumor Qudratilla qizi (Scientific Impulse, 2023)
This article deals with the data related to the etymological features of the means of realization of the semantics of “life” in Uzbek and English languages.